Disability studies and interdependence: an approach from contemporary political philosophy and the care economy - Castella Murillo, Jaren (2025)
This article examines the restructuring of the concept of autonomy demanded by critical disability studies, on the basis of the notions of intrinsic vulnerability, interdependence, and distributive justice, against the traditional liberal model of citizenship centered on self-sufficiency and productivity. It is argued that the hyperindependent subject underlying the classical social contract —heir to the Kantian and Cartesian tradition— does not describe an exceptional condition from which disability would be a deviation, but rather conceals, under the fiction of self-sufficiency, a dependency that runs through every human being at some point in their existence; recognizing that dependency as a universal condition, rather than as a biological anomaly or individual failure, requires replacing autonomy understood as non-interference with a relational autonomy exercised within networks of affection, assistance, and institutional support. From this ontological restructuring, the article examines the disability justice paradigm as an overcoming of paternalistic assistentialism and medical-rehabilitative models, with particular attention to supported decision-making models as opposed to substitute guardianship and to the recognition of the bidirectional agency of care. Finally, it discusses the institutional implications of this framework —universal accessibility, the decommodification of personal assistance, and applied intersectionality among ableism, poverty, gender, race, and migration— and examines two lines of future inquiry: the legal codification of the right to care, to be cared for, and to self-care, and the integration of disability into just ecological transition plans. To this end, it starts from a relational ontology of interdependence that replaces the fiction of self-sufficiency with the structural recognition of shared vulnerability.